Komodifikasi Makan Bajamba dalam Meningkatkan Pariwisata (Berkelanjutan) di Nagari Jawi-Jawi Guguak Kabupaten Solok - Iping Oktapika Naldi; Nopriyasman Nopriyasman; Diah Tyahaya Iman (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to examine the form and changes in the implementation of traditional makan bajamba and makan bajamba for tourism, so that their meaning and impact can be understood from a cultural studies perspective. This study was conducted using hegemony and deconstruction theories from a cultural studies perspective. The method used was descriptive qualitative. The data processing techniques used were field observation, interviews, and case documents. The finding of the study is makan bajamba tradition is grouped into important moments in the human life cycle, namely, makan bajamba at alek turun mandi, makan bajamba at weddings (alek mamantai kambiang and alek mamantai jawi), and makan bajamba at funerals (batagak penghulu). Meanwhile, makan bajamba for tourism, have the positive and negative impacts as well as the meanings that can be identified, namely religious, social, and cultural meanings, can be understood.